2019
DOI: 10.1080/20008198.2019.1606626
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oxytocin on the neural correlates of fearful face processing in PTSD related to childhood Trauma

Abstract: Background : Posttraumatic stress disorder (PTSD) related to exposure to abuse and neglect during childhood is associated with particularly severe and persistent deleterious outcomes. Amygdala hyperreactivity has been observed in childhood trauma survivors and implicated in symptoms of PTSD. Objective : The neuropeptide oxytocin holds promise as a potential treatment for PTSD due to its ability to attenuate amygdala response to threat cues. However, the effect of oxytocin on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 94 publications
(100 reference statements)
0
15
0
Order By: Relevance
“…An important focus of EJPT has also been the neural correlates underlying treatment interventions, including both novel pharmacotherapeutic (Flanagan et al, 2019;Kelmendi et al, 2016;Olff et al, 2015) and psychotherapeutic approaches (Lanius et al, 2015). Here, one study demonstrated altered electroencephalogram patterns before and after Eye Movement Desensitization and Reprocessing (EMDR) treatment in patients with breast cancer (Carletto et al, 2019).…”
Section: Neurobiology Of Ptsd: Neuroimaging and Neuroendocrine Developmmentioning
confidence: 99%
See 2 more Smart Citations
“…An important focus of EJPT has also been the neural correlates underlying treatment interventions, including both novel pharmacotherapeutic (Flanagan et al, 2019;Kelmendi et al, 2016;Olff et al, 2015) and psychotherapeutic approaches (Lanius et al, 2015). Here, one study demonstrated altered electroencephalogram patterns before and after Eye Movement Desensitization and Reprocessing (EMDR) treatment in patients with breast cancer (Carletto et al, 2019).…”
Section: Neurobiology Of Ptsd: Neuroimaging and Neuroendocrine Developmmentioning
confidence: 99%
“…The first studies on the bonding hormone oxytocin in our field began approximately a decade ago (Olff, 2012;Olff, Langeland, Witteveen, & Denys, 2010), with an exponential increase after that (e.g. Bui et al, 2019;Bradley, Davis, Wingo, Mercer, & Ressler, 2013;Flanagan et al, 2019;Frijling, 2017;Olff et al, 2015). The initial findings with regard to both prevention and treatment potential of intranasal oxytocin administration seem promising.…”
Section: Neurobiology Of Ptsd: Neuroimaging and Neuroendocrine Developmmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most prominent of these peptides is oxytocin, which appears to exert a regulatory effect on the cortisol response to stress ( Li et al, 2019 ; Winter and Jurek, 2019 ). In addition, it has been shown to reduce depressive symptoms following loss of a partner in animal models ( Bosch and Young, 2018 ), to reduce brain responses to fear-provoking visual stimuli in human suffering already exposed to trauma ( Flanagan et al, 2019 ), and to potentially enhance the likelihood of engaging in altruistic or pro-social behaviors ( Hurlemann, 2017 ). These effects are all relevant to the COVID-19 pandemic, where healthcare workers often experience interpersonal separation, social isolation, and a heightened exposure to fear-generating cues.…”
Section: Key Research Areas In the Neurobiology Of Resilience And Thementioning
confidence: 99%
“…Furthermore, severity of alcohol use and PTSD symptoms have been shown to impact self‐reported alcohol craving (Day et al, ; Kaczkurkin et al, ) and subjective alcohol cue–induced responses (Jasinska et al, ). While there is an emerging literature demonstrating a moderating effect of childhood trauma severity on oxytocin‐induced outcomes (Flanagan et al, ), the moderating effects of alcohol use and classic PTSD symptom severity on oxytocin response have not been explored. Therefore, we will test alcohol use and PTSD symptom severity scores as moderating predictors.…”
mentioning
confidence: 99%